Pengaruh Independence Commitment dan Orientasi Etika pada Intensi Melakukan Whistleblowing dengan Moral Reasoning menjadi Variabel Moderasi - Alfi Syahr, Oryza Daffa; Ashedica Pesudo, David Adechandra (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2021)
This study aimed to determine the effect of ethical orientation and independence commitment to the intention to do whistleblowing with moral reasoning as a moderating variable for active undergraduate students of the Faculty of Economics and Business, Universitas Kristen Satya Wacana. This study uses a quantitative descriptive approach, where a questionnaire is used as a research instrument. The sample technique used was purposive sampling in order to obtain a sample of 272 students as respondents in this study. The results of this study indicate that Independence commitment has a significant positive effect on the intention to do whistleblowing, with a low significant level, ethical orientation does not affect the intention to do whistleblowing, and moral reosing cannot moderate the relationship between the two independent variables on the intention to do whistleblowing on students for undergraduate students of Â Faculty of Economics and Business, Universitas Kristen Satya Wacana.